Nanosilica-Anchored Polycaprolactone/Chitosan Nanofibrous Bioscaffold to Boost Osteogenesis for Bone Tissue Engineering - Shengyou Ge; Xiaoyi Zhu; Chuanlong Zhang; Dongchen Jia; Wei Shang; Chao Ding; Jianping Yang; Yuanyong Feng (Molecules, 2022)
The strategy of incorporating bioactive inorganic nanomaterials without side effects as osteoinductive supplements is promising for bone regeneration. In this work, a novel biomass nanofibrous scaffold synthesized by electrospinning silica (SiO2) nanoparticles into polycaprolactone/chitosan (PCL/CS) nanofibers was reported for bone tissue engineering. The nanosilica-anchored PCL/CS nanofibrous bioscaffold (PCL/CS/SiO2) exhibited an interlinked continuous fibers framework with SiO2 nanoparticles embedded in the fibers. Compact bone-derived cells (CBDCs), the stem cells derived from the bone cortex of the mouse, were seeded to the nanofibrous bioscaffolds. Scanning electron microscopy and cell counting were used to observe the cell adhesion. The Counting Kit-8 (CCK-8) assay was used. Alkaline phosphatase (ALP), Alizarin red staining, real-time Polymerase Chain Reaction and Western blot tests were performed to confirm the osteogenesis of the CBDCs on the bioscaffolds. The research results demonstrated that the mechanical property of the PCL together with the antibacterial and hydrophilic properties of the CS are conducive to promoting cell adhesion, growth, migration, proliferation and differentiation. SiO2 nanoparticles, serving as bone induction factors, effectively promote the osteoblast differentiation and bone regeneration. This novel SiO2-anchored nanofibrous bioscaffold with superior bone induction activity provides a better way for bone tissue regeneration.